2022
DOI: 10.3390/cells11243994
|View full text |Cite
|
Sign up to set email alerts
|

PICALM and Alzheimer’s Disease: An Update and Perspectives

Abstract: Genome-wide association studies (GWAS) have identified the PICALM (Phosphatidylinositol binding clathrin-assembly protein) gene as the most significant genetic susceptibility locus after APOE and BIN1. PICALM is a clathrin-adaptor protein that plays a critical role in clathrin-mediated endocytosis and autophagy. Since the effects of genetic variants of PICALM as AD-susceptibility loci have been confirmed by independent genetic studies in several distinct cohorts, there has been a number of in vitro and in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 164 publications
0
30
0
Order By: Relevance
“…In contrast, very recently, Kisler et al reported that early artesunate (32 mg/kg/day) treatment for 2 months increased blood serum Aβ 42 and Aβ 40 levels by approximately two-fold, suggesting the accelerated clearance of Aβ from brain-toblood in 5-month-old 5XFAD mice that correlated with a reduced Aβ pathology and improved behavioral performance in cognition tests [76]. In this study, it was demonstrated that artesunate specifically increased endothelial PICALM (phosphatidylinositol-binding clathrin assembly protein) levels, a protein that interacts with LRP1 and is involved in internalization of cell surface receptors, as well as in intracellular trafficking of different proteins [154]. It is noteworthy that a 60% reduction in PICALM endothelial levels was measured in human AD brains, correlating inversely with the Aβ load, Braak stage, and clinical dementia, leading to the proposal of a change in the endothelial PICALM level as a significant susceptibility factor for late-onset AD [154].…”
Section: Blood-brain Barriermentioning
confidence: 81%
“…In contrast, very recently, Kisler et al reported that early artesunate (32 mg/kg/day) treatment for 2 months increased blood serum Aβ 42 and Aβ 40 levels by approximately two-fold, suggesting the accelerated clearance of Aβ from brain-toblood in 5-month-old 5XFAD mice that correlated with a reduced Aβ pathology and improved behavioral performance in cognition tests [76]. In this study, it was demonstrated that artesunate specifically increased endothelial PICALM (phosphatidylinositol-binding clathrin assembly protein) levels, a protein that interacts with LRP1 and is involved in internalization of cell surface receptors, as well as in intracellular trafficking of different proteins [154]. It is noteworthy that a 60% reduction in PICALM endothelial levels was measured in human AD brains, correlating inversely with the Aβ load, Braak stage, and clinical dementia, leading to the proposal of a change in the endothelial PICALM level as a significant susceptibility factor for late-onset AD [154].…”
Section: Blood-brain Barriermentioning
confidence: 81%
“…There are significant associations between several SNPs in the PICALM locus with AD-related phenotypes such as the age of onset, hippocampal atrophy, cognitive functions, and tau or Aβ levels in CSF [ 30 ]. Numerous and independent GWAS have identified several SNPs in the PICALM gene that are strongly associated with LOAD, the most significant being rs3851179 [ 54 ]. Compared to subjects with no NDDs, PICALM mRNA levels are high in the blood and brain in patients with AD and are downregulated in patients with PD [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…SEC BDEVs are enriched in AD associated molecules, such as CLU, PICALM and LRP1 (Bellenguez et al., 2022). PICALM plays a critical role in clathrin‐mediated endocytosis and autophagy (Ando et al., 2022) and is involved in the clearance of amyloid‐β peptide (Storck et al., 2018). We also found SEC BDEVs are enriched for astrocyte‐derived EV as we previously reported (You et al., 2019) and enriched for LRP1, which is a novel astrocyte‐derived EV marker that can distinguish EVs from distinct subsets of other neuronal cells (You et al., 2022).…”
Section: Discussionmentioning
confidence: 99%